The POU Transcription Factor Oct-1 Represses Virus-Induced Interferon A Gene Expression - Mesplède, Thibault (American Society for Microbiology, 2005)
Alpha interferon (IFN-α) and IFN-β are able to interfere with viral infection. They exert a vast array of biologic functions, including growth arrest, cell differentiation, and immune system regulation. This regulation extends from innate immunity to cellular and humoral adaptive immune responses. A strict control of expression is needed to prevent detrimental effects of unregulated IFN. Multiple IFN-A subtypes are coordinately induced in human and mouse cells infected by virus and exhibit differences in expression of their individual mRNAs. We demonstrated that the weakly expressed IFN-A11 gene is negatively regulated after viral infection, due to a distal negative regulatory element, binding homeoprotein pituitary homeobox 1 (Pitx1). Here we show that the POU protein Oct-1 binds in vitro and in vivo to the IFN-A11 promoter and represses IFN-A expression upon interferon regulatory factor overexpression. Furthermore, we show that Oct-1-deficient MEFs exhibit increased in vivo IFN-A gene expression and increased antiviral activity. Finally, the IFN-A expression pattern is modified in Oct-1-deficient MEFs. The broad representation of effective and potent octamer-like sequences within IFN-A promoters suggests an important role for Oct-1 in IFN-A regulation.